Kepemimpinan Transformasional Mudir Ma’had Dalam Meningkatkan Loyalitas Tenaga Pengajar Di Pondok Pesantren Al Khairat Bekasi Timur - Achmad Saifulloh; Akhmad Fauzi Hamzah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the role of transformational leadership by the Mudir in strengthening teacher loyalty and professionalism at Pondok Pesantren Al Khairat Bekasi Timur. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis, with validation ensured via triangulation. Data analysis followed the Miles and Huberman interactive model. Findings indicate that the Mudir’s leadership, aligned with Bass and Avolio’s four dimensions—idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration—effectively fosters teacher loyalty. Loyalty manifests not only in administrative compliance but also in emotional commitment, long-term dedication, and active participation in decision-making, rooted in Islamic values of khidmah, spiritual bonding, and syura. This study confirms that transformational leadership based on Islamic principles is key to enhancing teacher professionalism and institutional loyalty in pesantren education.